Análisis de la comunicación digital y el uso estratégico de las redes sociales de las cadenas farmacéuticas: Farmacias Mia, Farmacias Cuxibamba y Asociación de Farmacias (Asofil) periodo Mayo-Julio 2021. - Arrobo Samaniego, Claudia Nathaly (2022)
At present, the use of digital media for the communication of a company is very important, since it provides advantages that traditional media do not. The cost of advertising is lower and the audience scope is greater. Digital communication is a tool used for growth and commercial competitiveness. For this reason, pharmaceutical companies are also communicating through these means. Small or medium-sized companies (SMEs) face disadvantages compared to large companies, because they do not have specialized departments to handle this form of communication or online advertising. National and local chains have more appropriated ways of communication. For instance, Farmacias Cuxibamba and Farmacias Mia, which are large pharmaceutical chains and are the strong competition of the independent pharmacies that belong to Asociación of Farmacias de Loja (ASOFIL). It is important to analyze the digital strategies that these companies have used to achieve positioning on the web. According to this, the objective of this research is to analyze digital communication and the strategic use of social networks of the aforementioned pharmaceutical chains for three months, in order to answer the following question: How do the pharmaceutical chains selected for this study manage their digital communication? And, which are the strategies applied in their social networks? To find out the answer these questions we will use research techniques such as: observation files, interviews, surveys, and metric analysis software. Research methodologies and tools made it possible to collect the necessary information to understand the strategies applied and those that would be lacking to improve digital communication. Now, based on the results obtained, key strategies are determined and developed for the pharmaceutical chains studied in order to carry out a strategic digital communication plan, which will serve to strengthen ASOFIL's social media management Keywords: Loja Pharmacy Association; Digital Communication; Digital Communication Strategies; Digital networks.